2004
DOI: 10.1007/s00428-004-1018-0
|View full text |Cite
|
Sign up to set email alerts
|

BRAF mutations typical of papillary thyroid carcinoma are more frequently detected in undifferentiated than in insular and insular-like poorly differentiated carcinomas

Abstract: Somatic mutations of the BRAF gene (BRAFV599E and BRAFK600E) were found to be closely associated with different histotypes of papillary thyroid carcinoma (PTC). The V599E mutation is highly prevalent in PTC with a papillary or mixed papillary follicular growth pattern, and the K600E mutation is apparently restricted to the follicular variant of PTC. It is usually accepted that thyroid malignancies may follow a progression path from well-differentiated to poorly differentiated (PDC) and undifferentiated (UC) ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(66 citation statements)
references
References 22 publications
3
59
1
2
Order By: Relevance
“…Similarly, the BRAF V600E mutation has been frequently found in microcarcinomas of the thyroid (30), which suggests a role in tumor initiation rather than tumor progression. On the other hand, BRAF mutations are also found in poorly differentiated and anaplastic thyroid carcinomas, suggesting that they may play a role in their highly aggressive behavior (7,11,39,40). In the study of Nikiforova et al (7), all BRAF-mutant poorly differentiated and anaplastic carcinomas contained areas of preexisting papillary carcinoma, and the BRAF V600E mutation was present in both the well-differentiated and dedifferentiated components, suggesting that it may have contributed to the transition from PTC to anaplastic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the BRAF V600E mutation has been frequently found in microcarcinomas of the thyroid (30), which suggests a role in tumor initiation rather than tumor progression. On the other hand, BRAF mutations are also found in poorly differentiated and anaplastic thyroid carcinomas, suggesting that they may play a role in their highly aggressive behavior (7,11,39,40). In the study of Nikiforova et al (7), all BRAF-mutant poorly differentiated and anaplastic carcinomas contained areas of preexisting papillary carcinoma, and the BRAF V600E mutation was present in both the well-differentiated and dedifferentiated components, suggesting that it may have contributed to the transition from PTC to anaplastic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…When multi-step carcinogenesis is taken into account, a considerable number of anaplastic carcinomas with BRAF mutations should be found. In previous reports, however, the frequency of the BRAF mutation was only about 10% on average and ranged from 0 to 63% (Fukushima et al, 2003;Namba et al, 2003;Nikiforova et al, 2003;Begum et al, 2004;Soares et al, 2004;Xing et al, 2004;Quiros et al, 2005). Among these studies, some reported that the BRAF mutation is found frequently only in anaplastic carcinomas with a papillary carcinoma component, although these studies have examined only four or five cases.…”
mentioning
confidence: 94%
“…However, as noted above, an association between BRAF mutations and aggressive tumour behaviour has not been demonstrated in all populations, making the clinical relevance of this association uncertain. It is also of interest that the incidence of BRAF V600E mutations in undifferentiated anaplastic thyroid cancer is similar to that in well-differentiated early-stage tumours in several studies (Namba et al, 2003;Nikiforova et al, 2003;Begum et al, 2004;Soares et al, 2004;Trovisco et al, 2004;Trovisco et al, 2005) supporting the concept that some anaplastic thyroid cancers arise from more typical forms of PTC and suggesting that BRAF signalling may be functionally important in anaplastic thyroid cancers. These data also suggest that BRAF mutations may not be independently sufficient to induce dedifferentiation.…”
Section: Braf Mutations In Aggressive Ptcmentioning
confidence: 86%